A Review on the Parameters Affecting the Mechanical, Physical, and Thermal Properties of Natural/Synthetic Fibre Hybrid Reinforced Polymer Composites - DO Bichang’a; FO Aramide; IO Oladele; OO Alabi (Advances in Materials Science and Engineering)
The global drive towards a circular economy that emphasizes sustainability in production processes has increased the use of agro-based raw materials like natural fibres in applications that have long been dependent on inorganic raw materials. Natural fibres provide an eco-friendly, more sustainable, and low cost alternative to synthetic fibres that have been used for a long time in the development of composite materials. However, natural fibres are associated with high water absorption capacity due to their hydrophilic nature leading to poor compatibility with hydrophobic polymeric matrices, thus lower mechanical properties for various applications. Hybridization of natural fibres with synthetic fibres enhances the mechanical performance of natural fibres for structural and nonstructural applications such as automobile, aerospace, marine, sporting, and defense. There have been increased research interests towards natural/synthetic fibre hybrid composites in the past two decades (2001–2021) to overcome the identified limitations of natural fibres. Therefore, understanding the parameters affecting the properties and potential of using natural and synthetic fibre reinforcements to develop hybrid composites is of great interest. The review showed that using appropriate fibre orientation, fibre weight fraction and stacking sequence yields good mechanical, physical, and thermal properties that are competitive with what only synthetic fibre reinforced composites can achieve. In addition, these properties can be improved through pretreatment of natural fibres using different chemicals. This paper provides in review form the parameters affecting the mechanical, physical, and thermal properties of natural/synthetic fibre hybrid reinforced polymer composites from the year 2001 to 2021.